Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10639-021-10724-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of granular simulation for integrating computational thinking into computational physics courses

Abstract: Computational thinking (CT) is an essential skill in the twenty-first century. The computational physics course (CPC) is one subject that is designed to support students in the practice of CT. Many studies show that the worksheets could be a solution in a CPC as a scaffold to achieve the CT objectives both online and offline. The study aims to develop the worksheet and integrate it with CT in a computational physics course. This study applied the research and development (R & D) method with the ADDIE model app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Azevedo and Hadwin (2005) suggested that the contexts in which scaffolding is applied to computer science education are “demonstration,” “conceptual learning,” “technology-assisted teaching,” “teacher-student debate,” “student self-learning skills,” and “metacognition.” To learn computational thinking, educational games need to provide feedback mechanisms and scaffolding to help learners master computational thinking (Lee et al, 2019). Muliyati et al (2022), in their study, incorporated computational thinking into physics instruction and used the three dimensions of computational thinking (abstraction, algorithms, and generalization) as scaffolding for the computational thinking curriculum to help students learn new knowledge, showing that the inclusion of scaffolding significantly improved the overall computational thinking skills of students. In view of the above, scaffolding support is necessary in the learning of computational thinking to support learners in performing tasks and acquiring skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Azevedo and Hadwin (2005) suggested that the contexts in which scaffolding is applied to computer science education are “demonstration,” “conceptual learning,” “technology-assisted teaching,” “teacher-student debate,” “student self-learning skills,” and “metacognition.” To learn computational thinking, educational games need to provide feedback mechanisms and scaffolding to help learners master computational thinking (Lee et al, 2019). Muliyati et al (2022), in their study, incorporated computational thinking into physics instruction and used the three dimensions of computational thinking (abstraction, algorithms, and generalization) as scaffolding for the computational thinking curriculum to help students learn new knowledge, showing that the inclusion of scaffolding significantly improved the overall computational thinking skills of students. In view of the above, scaffolding support is necessary in the learning of computational thinking to support learners in performing tasks and acquiring skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They enable systematic problem-solving, algorithmic thinking, and critical analysis [9]. These skills find applications across various fields, including computer science, data analysis, and automation [10], [11]. They foster innovation, enhance education, create career opportunities, and contribute to global competitiveness.…”
Section: Introductionmentioning
confidence: 99%